Strengthening Mindset and Entrepreneurial Attitudes in Facing Challenges through Kenduri Budaya Benteng Tujuh Lapis in Rokan Hulu Regency - Alfa Syahputra; Junifar Akmal; Fitra Mulya; Willi Meilita; Toni Ahmad Subekti; Nurmala Sari (Devotion : Journal of Research and Community Service, 2026)
This community service activity aims to strengthen the entrepreneurial mindset and attitudes of the community in facing various social and economic challenges through a local cultural approach. The activity was carried out as part of the Kenduri Budaya Benteng Tujuh Lapis series, with the author serving as a speaker on the theme of Entrepreneur: Mindset and Attitude in Facing Challenges. The activity was held at the Benteng Tujuh Lapis Tuanku Tambusai, Dalu-Dalu, Luhak Tambusai, Rokan Hulu Regency, Riau Province. It was organized by the Cultural Preservation Center (Balai Pelestarian Kebudayaan/BPK) Region IV of Riau and the Riau Islands, in collaboration with LKA Luhak Tambusai. Implementation methods included educational lectures, interactive discussions, and a participatory approach. The results demonstrated an increase in participants' understanding of the importance of a positive mindset, adaptive attitude, and psychological resilience as the foundational pillars of entrepreneurship in navigating challenges and leveraging local cultural potential in a sustainable manner. The implication of this activity is the development of a community empowerment model that integrates local cultural values with entrepreneurship education, which may be replicated in other regions with comparable cultural richness.